Intelligent human systems integration : proceedings of the 1st International Conference on Intelligent Human Systems Integration (IHSI 2018) : integrating people and intelligent systems, January 7-9, 2018, Dubai, United Arab Emirates /: proceedings of the 1st International Conference on Intelligent Human Systems Integration (IHSI 2018) : integrating people and intelligent systems, January 7-9, 2018, Dubai, United Arab Emirates. (2018) - Unknown
No abstract available